Genotypic differences in physiological and biochemical responses to salinity stress in melon (Cucumis melo L.) plants Prospects for selection of salt tolerant landraces - Sarabi, Behrooz (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.